Energetic evaluation of hydrogen refueling stations with liquid or gaseous stored hydrogen. (8th March 2019) - Bauer, Artur; Mayer, Thomas; Semmel, Malte; Guerrero Morales, Martin Alberto; Wind, Joerg
Abstract: The future success of fuel cell electric vehicles requires a corresponding infrastructure. In this study, two different refueling station concepts for fuel cell passenger cars with 70 MPa technology were evaluated energetically. In the first option, the input of the refueling station is gaseous hydrogen which is compressed to final pressure, remaining in gaseous state. In the second option, the input is liquid hydrogen which is cryo-compressed directly from the liquid phase to the target pressure. In the first case, the target temperature of −33 °C to −40 °C[1] is achieved by cooling down. In the second option, gaseous deep-cold hydrogen coming from the pump is heated up to target temperature. A dynamic simulation model considering real gas behavior to evaluate both types of fueling stations from an energetic perspective was created. The dynamic model allows the simulation of boil-off losses (liquid stations) and standby energy losses caused by the precooling system (gaseous station) dependent on fueling profiles. The functionality of the model was demonstrated with a sequence of three refueling processes within a short time period (high station utilization). The liquid station consumed 0.37 kWh/kg compared to 2.43 kWh/kg of the gaseous station. Rough estimations indicated that the energy consumption of the entire pathway is higher for liquid hydrogen. The analysis showed the high influence of the high-pressure storage system design on the energy consumption of the station. For future research work the refueling station model can be applied to analyze the energy consumption dependent on factors like utilization, component sizing and ambient temperature. Highlights: An energetic hydrogen refueling station simulation model was built and demonstrated. Real gas behavior by Helmholtz free energy with highest accuracy was applied. Main components of stations with liquid and gaseous stored hydrogen were compared. Conditioning initially liquid hydrogen consumes less energy than gaseous hydrogen. The model allows to evaluate and compare both concepts under various conditions.